Monotonic direct simple shear tests on sand under multidirectional loading - Li, Yao; Yang, Yunming; Yu, Hai-Sui; Roberts, Gethin Wyn (American Society of Civil Engineers, 2016)
Stress–strain responses of Leighton Buzzard sand are investigated under bidirectional shear. The tests are conducted by using the variable direction dynamic cyclic simple shear (VDDCSS), which is manufactured by Global Digital Systems (GDS) Instruments Ltd., U.K. Soil samples are anisotropically consolidated under a vertical normal stress and horizontal shear stress and then sheared in undrained conditions by applying a horizontal shear stress acting along a different direction from the consolidation shear stress. The influence of the orientation and magnitude of the consolidation shear stress is investigated in this study. There are only a few previous studies on soil responses under bidirectional shear, of which most studies do not consider the impact of the magnitude of the consolidation shear stress. They are compared with current studies, indicating both similarities and differences. Generally, all test results indicate that a smaller angle between the first and second horizontal shear stress leads to more brittle responses with higher peak strengths, and a larger angle leads to more ductile responses. In addition, the consolidation shear tends to make soil samples denser, and both the magnitude of consolidation shear stress and its direction influence the following stress–strain responses of soil samples.